When do movements against femicide succeed? the cases of Mexico and Turkey - Aydın, Rana Elif. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in Social Sciences, 2022., 2022)
Femicide refers to the killing of women because of their gender and is the deadliest form of violence against women. Data shows that it exists in every country around the world. While some of these countries may be deadlier for women than others, few stand out for their strong mobilization against the issue. In this thesis, I try to pinpoint when movements against femicide succeed by using the feminist and the subsequent antifemicide movements in Mexico and Turkey as my cases. Previous research shows that social movements have a higher chance of success in times and spaces where political opportunity structures exist. This thesis aims to clarify whether political opportunities have been conducive to the success of antifemicide movements. To test that hypothesis, I first trace the emergence of antifemicide movements in both cases through qualitative methods. While outlining these movements, I point out when these movements have achieved success based on the theory of political opportunities. Then, through a wide historic lens, I define what success means for a movement and the circumstances of the turning points that allow the movement the gain traction or achieve success. As a result, I find that antifemicide movements are compatible with the political opportunity paradigm, but only when an expanded definition of political opportunities is used. With that definition in place, I argue that political opportunities that present in various forms are conducive to the success of movements against femicide.
Keywords: Women -- Crimes against -- Turkey.; Women -- Crimes against -- Mexico.